2013
DOI: 10.1021/es4048329
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Field Concentrations Exceed FOCUS Surface Water Predictions: Urgent Need of Model Improvement

Abstract: FOCUS models are used in European regulatory risk assessment to predict the frequency and magnitude of individual pesticide surface water concentrations. A recent study showed that these models are not protective in the prediction of insecticide concentrations in surface waters and sediments. Since fungicides differ with regard to their physicochemical properties, application patterns, and entry routes, we compared a larger data set of 417 measured field concentrations (MFC) of agricultural fungicides in surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…However, other reasons not concerning aquatic organisms (e.g., high mammalian and avian toxicities of organophosphates) presumably led to the withdrawal of hazardous pesticide compounds under Directive 91/414/ EEC, so that the overall environmental risks might nonetheless be reduced over time (Cross and Edward-Jones 2011). Overall, our data and those of Knäbel et al (2012Knäbel et al ( , 2014 indicate that a critical reconsideration of the entire EU pesticide regulatory risk assessment approach including enforcement of mandatory risk mitigation obligations is imperatively needed; these findings must be seriously considered in future revisions of EU pesticide regulations. In addition, effective risk mitigation measures (e.g., Reichenberger et al 2007;Stehle et al 2011) have to be implemented and enforced, inter alia within National Action Plans, as requested by EU Directive 2009/128/EC (Sustainable Use Directive for Plant Protection Products (European Commission 2009b)).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, other reasons not concerning aquatic organisms (e.g., high mammalian and avian toxicities of organophosphates) presumably led to the withdrawal of hazardous pesticide compounds under Directive 91/414/ EEC, so that the overall environmental risks might nonetheless be reduced over time (Cross and Edward-Jones 2011). Overall, our data and those of Knäbel et al (2012Knäbel et al ( , 2014 indicate that a critical reconsideration of the entire EU pesticide regulatory risk assessment approach including enforcement of mandatory risk mitigation obligations is imperatively needed; these findings must be seriously considered in future revisions of EU pesticide regulations. In addition, effective risk mitigation measures (e.g., Reichenberger et al 2007;Stehle et al 2011) have to be implemented and enforced, inter alia within National Action Plans, as requested by EU Directive 2009/128/EC (Sustainable Use Directive for Plant Protection Products (European Commission 2009b)).…”
Section: Discussionmentioning
confidence: 57%
“…The tier-I RAC SW associated with higher-tier RAC SW (n (insecticides): 13, median RAC SW =0.003 μg/L) denote RAC SW derived from the first tier risk assessment for insecticides, which were finally approved using highertier studies (microcosms/mesocosms, see Table 1) Nienstedt et al (2012) argued that the protection of ecosystem services for the fulfillment of the specific protection goals requires the protection of biodiversity in agricultural landscapes; our data, however, indicate clear biodiversity impairments (see also Stehle and Schulz 2015) in agricultural surface waters due to insecticide exposure. Importantly, not only the endpoints of the regulatory effect assessment (i.e., RAC) are exceeded in the field but also those of the regulatory exposure assessment (i.e., PEC; Knäbel et al 2012;Knäbel et al 2014); it must therefore be concluded that the current pre-authorization regulatory risk assessment schemes including associated risk mitigation obligations (i.e., pesticide application prescriptions) and underlying EU pesticide regulations, do not protect the aquatic environment. In addition, the insecticide field exposure data presented here do not provide a final conclusion on the reasons for RAC exceedances in the field, i.e., the failure of the prospective regulatory exposure and risk assessment or of farmers' adherence to regulatory risk mitigation obligations such as no-spray buffers; however, Knäbel et al (2012) suggest both factors' contributions to insecticide risks for EU surface waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, taken together the results of our and two additional studies (Bereswill et al, 2012(Bereswill et al, , 2013, all performed in completely different agro-environmental settings, clearly challenge this risk management option for predicted runoff-related pesticide exposure of surface waters currently applied in the regulatory authorization process of many pesticides. These findings on shortcomings of the basic regulatory risk management assumptions may thus explain the large extent of pesticide field concentrations, which exceeded higher-tier PECs (Knäbel et al, 2012(Knäbel et al, , 2014 and RTLs Schulz, 2015a, 2015b) set for official pesticide authorization. We thus conclude that the field-relevance, effectiveness and protectiveness of buffer strip-related mitigation options employed in the prospective regulatory risk assessment procedures should be thoroughly reconsidered in order to reduce adverse environmental side-effects arising from current and future agricultural pesticide use.…”
Section: Implications For the Regulatory Pesticide Risk Assessmentmentioning
confidence: 93%
“…However, recent studies proved that pesticide surface water concentrations often exceed regulatory risk assessment endpoints for both exposure (i.e., the predicted environmental concentrations (PEC) derived from exposure modeling; Knäbel et al, 2012Knäbel et al, , 2014 and effects (i.e., the regulatory threshold levels (RTL), which represent ecologically acceptable pesticide concentrations; Schulz, 2015a, 2015b). Pesticides thus pose a severe threat to the biodiversity and integrity of aquatic ecosystems (Beketov et al, 2013;Stehle and Schulz, 2015a).…”
Section: Introductionmentioning
confidence: 99%